Study on wind energy potential for agricultural water pumping system in the middle part of Thailand - Chamlong Prabkeao; Akapot Tantrapiwat (My University, 2018)
A study on wind powered water pumping system aimed for agriculture was carried out in the middle part of Thailand. In this alluvial plain, wind energy potential was determined by making a survey on 21 observation sites. The survey was made in a period of one year, and it has shown that this region locates in a clam climate zone with average wind speeds at about 2 m/s. A wind turbine-water pumping system was installed and evaluated for its performance and efficiency. The result has shown a linear relationship between water discharge capability and the wind speeds. Due to the type of turbine and low wind speed in this region, the system efficiency turned out to be minimal, yet it was practical because the wind power was free. A simple cost analysis from the survey data also has shown that using a wind turbine in this region will be worthwhile when it can be operated for about two decades.
Keywords: Water pumping; Hybrid Renewable Energy Systems